2005
DOI: 10.1093/ejo/cji083
|View full text |Cite
|
Sign up to set email alerts
|

Development of a questionnaire for assessment of the psychosocial impact of dental aesthetics in young adults

Abstract: The aim of this study was to develop a psychometric instrument for assessment of orthodontic-specific aspects of quality of life. The study subjects, 194 young adults aged 18-30 years, were interviewed using a pool of 23 items dealing with the psychosocial impact of dental aesthetics. Self- and interviewer-rating of the dental aesthetic appearance of each subject were carried out using the Aesthetic Component (AC) of the Index of Orthodontic Treatment Need (IOTN). Additionally, the Perception of Occlusion Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
285
1
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(307 citation statements)
references
References 27 publications
11
285
1
10
Order By: Relevance
“…6,18,22 Most adolescents (98.3%) had some level of psychosocial impact of dental esthetics, and a significant percentage of the sample (34.6%) revealed dissatisfaction with their dental appearance. Although it is true that increased teeth display has more chance for an increased perception of malocclusion (because teeth in malocclusion are more visible), teeth or gingival display itself is an esthetic problem that can cause psychosocial effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,18,22 Most adolescents (98.3%) had some level of psychosocial impact of dental esthetics, and a significant percentage of the sample (34.6%) revealed dissatisfaction with their dental appearance. Although it is true that increased teeth display has more chance for an increased perception of malocclusion (because teeth in malocclusion are more visible), teeth or gingival display itself is an esthetic problem that can cause psychosocial effects.…”
Section: Discussionmentioning
confidence: 99%
“…18,23,24 The impact of oral health conditions on a person's satisfaction with their appearance might result in shame in social contacts and psychosocial disadvantage. 18,23,24 In a previous study, de Paula-Junior et al 4 showed that adolescents' self-perceived impact of dental esthetics is influenced by the severity of malocclusion, oral health-related quality of life, and body satisfaction. Multiple regression analysis revealed significant associations of independent variables (DAI, short form of the Oral Health Impact Profile, and body satisfaction scale) with the PIDAQ scale and subscales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, authors have modified generic OHRQoL questionnaires that were originally developed to measure the impact of malocclusion on quality of life, (28) orthodontic-specific aspects on quality of life (e.g. psychosocial impact of dental aesthetics), (29) or the impact of pain during treatment on quality of life. (30) Moreover, previously published valid and reliable questionnaires have limitations, for example some of these questionnaires are age specific (28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Comparison With Other Questionnairesmentioning
confidence: 99%
“…psychosocial impact of dental aesthetics), (29) or the impact of pain during treatment on quality of life. (30) Moreover, previously published valid and reliable questionnaires have limitations, for example some of these questionnaires are age specific (28)(29)(30)(31)(32)(33)(34)(35)(36). Other limitations are related to the aims of existing questionnaires developed for cross-sectional use to measure either motivation, expectations, experiences, or satisfaction (28-37).…”
Section: Comparison With Other Questionnairesmentioning
confidence: 99%